2013
DOI: 10.1021/np400099m
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Antinociceptive Activity of Epiisopiloturine, an Imidazole Alkaloid Isolated from Pilocarpus microphyllus

Abstract: The aim of this study was to investigate the antinociceptive and anti-inflammatory activities of epiisopiloturine (1), an imidazole alkaloid found in the leaves of Pilocarpus microphyllus. The anti-inflammatory activity of 1 was evaluated using several agents that induce paw edema and peritonitis in Swiss mice. Paw tissue and peritoneal fluid samples were obtained to determine myeloperoxidase (MPO) activity or tumor necrosis factor (TNF)-α and interleukin (IL)-1β levels. The antinociceptive activity was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 41 publications
6
44
0
6
Order By: Relevance
“…The anti-migraine effect of ANE is probably through its action on bradykinin receptors (B1 or B2) and inhibiting PPE and vocalization in rats. As the alkaloids from other plant shown to be effective in inhibiting bradykinin receptors (Silva et al, 2013), the observed protective effect could be via antagonism of bradykinin receptors by alkaloids from ANE. Thus the alkaloids from ANE might possess the anti-migraine potential and could be the future specific target molecule for evaluation of anti-migraine properties.…”
Section: Discussionmentioning
confidence: 98%
“…The anti-migraine effect of ANE is probably through its action on bradykinin receptors (B1 or B2) and inhibiting PPE and vocalization in rats. As the alkaloids from other plant shown to be effective in inhibiting bradykinin receptors (Silva et al, 2013), the observed protective effect could be via antagonism of bradykinin receptors by alkaloids from ANE. Thus the alkaloids from ANE might possess the anti-migraine potential and could be the future specific target molecule for evaluation of anti-migraine properties.…”
Section: Discussionmentioning
confidence: 98%
“…was injected to the positive and negative control groups. After acetic acid administration, for 20 min the number of writhes was counted [22,23]. The extracts and acetylsalicylic acid suspended in tween 80 prior to administration and given orally.…”
Section: Analgesic Activitymentioning
confidence: 99%
“…Anti‐inflammatory and antinociceptive activities were evaluated in acute inflammation and nociception models (1 mg/kg, i.p.) such as carrageenan‐induced paw oedema, acetic acid‐induced writhing, hot plate and the formalin tests in mice . The antinociceptive effect of EPI seems to be partially mediated by the activation of the opioid receptors, while the anti‐inflammatory effect occurred by the reduction in the paw oedema and decrease in leucocyte migration, and TNF‐α and IL‐1β levels in the peritoneal cavity .…”
Section: Introductionmentioning
confidence: 99%